Pengembangan Smart App Creator untuk Meningkatkan Literasi Peserta Didik pada Mata Pelajaran IPS di Sekolah Dasar - Nur Arif MS (Jurnal Didaktika Pendidikan Dasar, 2023)
The reading literacy ability of the fifth grade PAM Pilot State Elementary School students is low because their willingness to read is also low. This study aims to develop learning media to increase students' reading interest. The media developed is the Smart App Creator which contains material on cultural diversity in South Sulawesi Province. This research is for the fifth grade students of the PAM Pilot State Elementary School for the 2020/2021 academic year. This research method is the Research and Development research method referring to the ADDIE development model (analyze, design, development, implementation, evaluation). The results obtained from the response questionnaire are 6 students or 21.43% good category, and 22 students or 78.57% very good category. Students gave a positive response to the Smart App Creator learning media in social studies subjects. The results of the literacy improvement test are 10 students or 35.71% with a score of 100, 5 students or 17.86% with a score of 90, and 13 students or 46,43% with a score of 80. From these results, it can be seen that there is an increase in the literacy of class students. V PAM Pilot State Elementary School uses the Smart App Creator learning media in social studies subjects